Estudo da cinética de sinterização assistida por micro-ondas de pós cerâmicos nano e submicrométricos, com diferentes propriedades dielétricas - Togashi, Marina Magro (2017)
Kinetic studies related to microwave assisted sintering of ceramic materials are scarce in the literature, as well as on a nanoscale and submicron scale. Therefore, the aim of this dissertation was to study microwave assisted sintering using an isothermal grain growth method for materials with different dielectric properties. The chosen materials (ZnO, Fe2O3 and TiO2) have technological and industrial importance and include a wide range of applications. The nanometric powders were synthesized by the sol-gel method and the submicron powders were purchased commercially. Initially, all powders were conformed and analyzed by conventional dilatometry at different heating rates, obtaining values of activation energy of the initial stage of sintering, using non-isothermal methods. After this study, the same powders were microwave sintered at different heating rates, and the study of sintering kinetics was carried out using an isothermal grain growth method, allowing the calculation of activation energy of grain growth. The results were compared for each material, in relation to the nano and submicron scales, the heating rate effect and the type of heating. The results obtained from microwave assisted sintering showed a tendency to decrease the final grain size with the increase of the heating rate. Moreover, for the submicron systems, the tendency was lower values of activation energy of grain growth, showing that the energy provided in the submicron systems favored densification. It was also observed that in materials with good dielectric properties, rapid densification occurred at temperatures lower than those observed in conventional heating, and in the case of ZnO, high diffusion coefficients helped densification. In the case of TiO2, the densification was affected, corroborating to be a poor absorber to microwave radiation.